PERNIKAHAN BEDA AGAMA DALAM PERSPEKTIF HUKUM ISLAM - Muallim Hasibuan (AL-ILMU, 2021)
Marriage in Islam is not merely an ordinary civil relationship or contract, but marriage is the Sunnah of the Prophet Muhammad, and the most suitable medium between Islamic religious guidance and instinctive or biological human needs that contain the meaning and values of worship. In Islamic marriage law, there is a principle known as the principle of selectivity. A person who wants to marry must first select who he can marry and with whom he is forbidden to marry. Even in customary law, it is actually known that there is a prohibition on marriage that is more specific than what is regulated by religion and legislation. In the patrilineal Batak society, men and women of the same clan/descendant are prohibited from marrying, if a Batak man wants to marry, he must look for another woman from another clan. It is not permissible for a woman to marry a woman who is out of Islam, she is not religious because she does not stay in her religion. He is not a Muslim because he is nothing more than an infidel like the Watsaniyah (idol worshipers), because marriage has character and has religious indications. The marriage of a Muslim man with a woman of the People of the Book who does not associate with Allah is permissible, but on the other hand the marriage of a Muslim woman with a man of the People of the Book is prohibited.